Innovative angiography: a new approach to discover more hepatic vein collaterals in patients with cirrhotic portal hypertension - Liu, Bowen; Yue, Zhendong; Cui, Ting; Zhao, Hongwei; Wang, Lei; Fan, Zhenhua; Wu, Yifan; Meng, Mingming; Zhang, Ke; Jiang, Li; Ding, Huiguo; Zhang, Yuening; et al. (BMC gastroenterology, 2023)
The hemodynamics of patients with cirrhosis and portal hypertension are complex and variable. We aimed to investigate differences in venous pressures determined by innovative angiography and conventional angiography using balloon occlusion of the hepatic veins in patients with alcoholic cirrhosis and portal hypertension. A total of 134 patients with alcoholic cirrhosis who fulfilled the inclusion criteria from June 2017 to June 2020 were included. During transjugular intrahepatic portosystemic shunt, conventional and innovative angiography were performed, and venous pressures were measured. A paired t-test and Pearson's correlation coefficient were used for analysis. Conventional and innovative hepatic angiography detected lateral branches of the hepatic vein in 26 (19.4%) and 65 (48.5%) cases, respectively (P < 0.001). Innovative angiography detected a total of 65 patients with lateral shunts, of whom 37 (56.9%) had initial shunts. The average wedged hepatic venous pressure and portal venous pressure of the initial lateral branches were 21.27 ± 6.66 and 35.84 ± 7.86 mmHg, respectively, with correlation and determination coefficients of 0.342 (P < 0.05) and 0.117, respectively. The mean hepatic venous pressure gradient and portal pressure gradient were 9.59 ± 7.64 and 26.86 ± 6.78 mmHg, respectively, with correlation and determination coefficients of 0.292 (P = 0.079) and 0.085, respectively. Innovative angiography reveals collateral branches of the hepatic veins more effectively than conventional angiography. Hepatic vein collateral branches are the primary factors leading to underestimation of wedged hepatic venous pressures and hepatic venous pressure gradients, with the initial hepatic vein collateral branches resulting in the most severe underestimations.